Effects of clam harvesting on sexual reproduction of the seagrass Zostera noltii - Alexandre, Ana (2005)
The sexual reproduction of Zostera noltii in the Ria Formosa lagoon (southern Portugal) was assessed by quantifying the variation in both flowering effort and evolution of maturation stages during the fertile season. The effects of clam harvesting on the sexual reproduction of Z. noltii were investigated using both descriptive and experimental approaches. Meadows disturbed by clam harvesting were compared with undisturbed meadows in 2 sectors of the lagoon. In both sectors, disturbed meadows showed significantly lower vegetative shoot density and significantly higher reproductive effort. The reproductive effort in the western disturbed meadows was 2-fold higher than in undisturbed meadows, whereas in eastern disturbed meadows it was 4-fold higher. In disturbed meadows, early maturation stages were found until the end of the flowering season and higher seed production was observed. Both the negative effect of clam harvesting on Z. noltii density and the positive effect on its reproductive effort were confirmed by manipulative field experiments. Plots that were experimentally harvested during the fertile season showed significantly lower vegetative shoot density and higher reproductive effort than unharvested plots. Results suggest that Z. noltii responds to clam harvesting disturbance by both increasing its reproductive effort and extending its fertile season.